On Origins and Implications of the Sovereign Debt Crisis in the Euro Area - MIRDALA, Rajmund; RUŠČÁKOVÁ, Anna (Journal of Advanced Studies in Finance; Vol 6 No 2 (2015): JASF Volume VI Issue 2(12) Winter 2015DO - 10.14505//jasf.v6.2(12).04, 2017)
The current crisis in the Euro Area is mostly a serious crisis of confidence. Its solutions have to be systematic and consistent. Our paper discusses its main systematic reasons while keeps in mind the European integration and globalization issues of the world economy and economic financial markets. Recent problems in the Euro area are based on the diagnostic of the origins of the balance of payments and self-fulfilling crisis, and discussed in the context of suggested remedies and solutions based on diversification of the monetary policy management in the EMU to eliminate the moral hazard from its financial sector, creation of a functioning system of fiscal transfers and finding a compromise between centralization and decentralization and government interventionism and “laissez faire”.